The health related quality of life in children admitted for cancer management and their families - Tembe, S’thembiso Charles (My University, 2020)
Children with cancer are treated in specialised hospital facilities, where the temporary environment may cause occupational disruption in the participation of normal occupations and therefore affecting the quality of life in both children and their parents. The parents who accompany the children while they are hospitalised often need to board near the hospital as the specialist unit is far from their homes which results in occupational disruption. Affecting family functioning. The aim of the study was to describe the health related quality of life (HRQoL) of children aged 8-12 years during their first admission to a specialised oncology unit and that of their parents. A quantitative, descriptive, cross-sectional study was conducted in Steve Biko Academic Hospital of 25 children with cancer and their parents, structured interviews were used with the children to determine their HRQoL in terms of their functioning and occupational disruption using the PedsQLTM Generic Core Scale (4.0) and their HRQoL related to the specifically to their diagnosis and treatment for cancer using the PedsQLTM Cancer Module (3.0). Their parents reported on their child’s HRQoL using proxy forms for these same instruments. The parents HRQoL in relation to family function was also determined for the using the PedsQLTM Family Impact Scale (2.0). Results indicate that most of the children were males with leukaemia, and treated with chemotherapy. The children and parents came from Gauteng and Mpumalanga provinces with low employment rates. Children and parents reported the children’s functioning and HRQoL to be at an intermediate level on the Generic Core Scale (4.0) except for physical functioning which parents felt was at a low level. Children scored change in school roles as having the greatest effect on their HRQoL. Scores on the Cancer Module (3.0) also indicated HRQoL at an intermediate level or at risk for impairment except for treatment anxiety and worry which from the children’s perspective fell in a high or normal range for HRQoL. This differed significantly from the parent’s perspective as they felt these aspects impacted on their and impaired child’s HRQoL along with procedural anxiety. Family function, particularly disruption of activities of daily living was reported by parents as impacting their HRQoL at an intermediate level with a marked decrease in physical functioning. Worry was at an impaired level for HRQoL while family relationships were at risk for impairment on the Family Impact Scale (2.0). No significant differences were found for HRQoL related to type of cancer or type of intervention provided. Children and parents were at risk for impairment of HRQoL with parents overestimating the effect of impairment except for treating anxiety and worry which from the children's perspective fell in a high or normal range for HRQoL, which is supported in the literature. The study indicates the need to understand the occupational disruption experienced by children hospitalised for the treatment of cancer and their parents to provide occupational therapy and intervention to facilitate HRQoL.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020